Sulfonic Acid Functionalized Ordered Mesoporous Silica and their Application as Highly Efficient and Selective Heterogeneous Catalysts in the Formation of 1, 2‐Monoacetone‐D‐glucose. Issue 24 (20th November 2018) - Krishna, Nunna V.; Anuradha, Sankaran; Ganesh, Reddi; Kumar, Velisoju V.; Selvam, Parasuraman
Abstract: A series of sulfonic acid functionalized ordered mesoporous silica (OMS), designated as RSO3 H‐OMS (R=alkyl or aryl; OMS=MCM‐41, IITM‐56 or SBA‐15), were prepared by post‐synthesis grafting method. These catalysts, in general, exhibit strong acidic sites and, therefore, yield diacetone‐ D ‐glucose as main product in the D ‐glucose acetonation reaction. On the other hand, the functionalized catalyst can also be tuned in such a way to generate significant amount of weak‐to‐moderate acidic sites, which are in turn responsible for the formation of 1, 2‐monoacetone‐ D ‐glucose, hitherto not reported so far. These functionalized materials also show promise as they are water tolerant catalyst as well as exhibit varying acidic strengths, which allow greater flexibility for the desired product. In addition, the uniform mesopores with high surface area permit bulkier molecules to enter the active sites, thus the catalyst offers larger pliability in terms of yield and reusability. We report here, for the first time, RSO3 H‐SBA‐15, with sizable amount of weak‐to‐moderate acidic sites, as a robust heterogeneous catalyst for the formation of the targeted molecule, 1, 2‐monoacetone‐ D ‐glucose. Abstract : O.M.S . The acidity and the strength of sulfonic acid functionalized ordered mesoporous silica (RSO3 H‐OMS) is found to be dependent on the nature and amount of silanol groups present on the surface of OMS used for grafting. By tuning their acidity, the product selectivity of acetonation of D ‐glucose can be altered.